2017
DOI: 10.21608/scumj.2017.46086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Safety of Thymoquinone Loaded on Gold Nanoparticles in the Treatment of Hamster Buccal Carcinogenesis

Abstract: Background: Oral cancer is one of the most prevalent cancers. Thymoquinone (TQ) has a potential therapeutic activity against cancer cells. Aim: This study aimed to compare the effect of TQ and TQ loaded on gold nanoparticles (GNPs) as systemic therapeutic agents through intra-peritoneal injection for 3&6 weeks after painting with DMBA (3 times/week for 14w). Material and Methods: This study was carried out on ninety male Syrian golden hamsters (n=90), its age ranged from 6 to 7 weeks, weighting 90-110 gm, purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In the present study, GII revealed increase in total WBCs (14x10 3 cells/ µl) compared to that of GI (8x10 3 cells/ µl), this reflected by extremely significant difference (p-value < 0.001), this is in line with that reported by Khan et al (2022) (37) This indicated the high local & systemic toxicity of DMBA in the hamster animal model. (22,28,38) Similarly, Leucocytosis is prevalent in individuals with progressive OSCC. as Tumor-related leukocytosis this results explained hematopoietic colony-stimulating factors and inflammatory cytokines Production of cytokines, chemokines and granule proteins promotes, which promotes tumor growth, angiogenesis, and increase its metastasis potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, GII revealed increase in total WBCs (14x10 3 cells/ µl) compared to that of GI (8x10 3 cells/ µl), this reflected by extremely significant difference (p-value < 0.001), this is in line with that reported by Khan et al (2022) (37) This indicated the high local & systemic toxicity of DMBA in the hamster animal model. (22,28,38) Similarly, Leucocytosis is prevalent in individuals with progressive OSCC. as Tumor-related leukocytosis this results explained hematopoietic colony-stimulating factors and inflammatory cytokines Production of cytokines, chemokines and granule proteins promotes, which promotes tumor growth, angiogenesis, and increase its metastasis potential.…”
Section: Discussionmentioning
confidence: 99%
“…Following that, the animals in GII (positive control) underwent no other medication, whereas those in GIII (cetuximab-3w) received cetuximab 1 mg/animal IP via insulin syringe at 3-day intervals for 3 weeks. (21,22) (Fig. 1B), whereas those in GIV (cetuximab-6w) were injected IP by insulin syringe with cetuximab 1 mg/animal at 3 days intervals for 6 weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…Those in GIV (TQ G): The animals were injected IP by insulin syringe (Fig. 1C) with TQ 50 mg/kg thrice a week for 3 ws (58) .…”
Section: Experimental Designmentioning
confidence: 99%
“…• Sub-group B3: Six animals were injected intraperitoneal with 0.001 GNPs-TQ/3 times/ week for six weeks 19 .…”
Section: Experimental Designmentioning
confidence: 99%